The long game [videorecording (DVD)] - Quintana, Julio; Quaid, Dennis; Hernandez, Jay, 1978-; Vigman, Gillian, 1972-; Works, Julian; Ortiz, Jaina Lee, 1986-; Cullen, Brett; Nuñez, Oscar, 1958-; Townshend, Hanan; Garcia, Humberto G. (Universal, 2024)
Follows five young Mexican-American caddies in 1955 who, fueled by their passion for golf, defy the odds by creating their own course in the South Texas desert. Despite facing outdated equipment and a lack of professional instruction, they triumph over wealthier, all-white teams to win the 1957 Texas State High School Golf Championship.